2006
DOI: 10.2471/blt.04.018663
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis screening in Mozambique

Abstract: Objective Programmes to control syphilis in developing countries are hampered by a lack of laboratory services, delayed diagnosis, and doubts about current screening methods. We aimed to compare the diagnostic accuracy of an immunochromatographic strip (ICS) test and the rapid plasma reagin (RPR) test with the combined gold standard (RPR, Treponema pallidum haemagglutination assay and direct immunofluorescence stain done at a reference laboratory) for the detection of syphilis in pregnancy. Methods We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Determine was the only test showing a statistically significant lower specificity among HIV positive specimens. This phenomenon has been described elsewhere [29] , [35] and may be the result of immune activation and subsequent deranged B-cell function in HIV [36] which presumably can lead to false positive tests. This is clearly important in settings such as Europe, USA and Australia where among gay men, up to 60% the syphilis infections are in HIV-positive individuals [37] [39] , such that approximately 1 in 6 reactive tests could be a false positive in this population.…”
Section: Discussionmentioning
confidence: 74%
“…Determine was the only test showing a statistically significant lower specificity among HIV positive specimens. This phenomenon has been described elsewhere [29] , [35] and may be the result of immune activation and subsequent deranged B-cell function in HIV [36] which presumably can lead to false positive tests. This is clearly important in settings such as Europe, USA and Australia where among gay men, up to 60% the syphilis infections are in HIV-positive individuals [37] [39] , such that approximately 1 in 6 reactive tests could be a false positive in this population.…”
Section: Discussionmentioning
confidence: 74%
“…Outlining the importance of good training, a study conducted in Mozambique demonstrated greater accuracy of POCTs when conducted by laboratory staff with intensive training, rather than when conducted by health care workers on bedside. Further, Balira et al [ 50 ] documented that only 25% of ANC staff in Tanzania received training in the prevention of syphilis mother-to-child transmission, in general [ 51 ]. Additionally, as countries begin to introduce syphilis POCTs, adequate quality assurance programmes must be established, which have been the norm for most laboratory syphilis screening programs but have frequently been neglected for POCTs [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted both this difficulty and the difficulty manipulating blood transfer devices. 14 , 20 23 …”
Section: Discussionmentioning
confidence: 99%